2014
DOI: 10.5455/ijmsph.2014.260120145
|View full text |Cite
|
Sign up to set email alerts
|

The role of computed tomography in blunt abdominal trauma as investigative tool conducted at tertiary level hospital, Vadodara

Abstract: Background: Evaluating patients who have sustained blunt abdominal trauma (BAT) remains one of the most challenging and resourceintensive aspects of acute trauma care. Missed intra-abdominal injuries continue to cause preventable deaths. Aims & Objective: To assess efficacy of CT scan (computed tomography) as accurate diagnostic tool for blunt abdominal trauma patients. Materials and Methods: 87 cases of blunt abdominal injury admitted in S.S.G hospital, Baroda during the period of August 2010 to November 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…No age group is exempted from traumatic injury of abdomen, but that it is more common in the second to fourth decade of life because this age represent working population. A similar incidence was reported by Vadodariya et al 3 and Mohapatra et al 9 Majority of our patients were male (Male: female= 2.3:1). The incidence of abdominal trauma in male population is higher because in our country males lead more active life and have more outdoor activities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…No age group is exempted from traumatic injury of abdomen, but that it is more common in the second to fourth decade of life because this age represent working population. A similar incidence was reported by Vadodariya et al 3 and Mohapatra et al 9 Majority of our patients were male (Male: female= 2.3:1). The incidence of abdominal trauma in male population is higher because in our country males lead more active life and have more outdoor activities.…”
Section: Discussionsupporting
confidence: 91%
“…Spleen was the most common organ to be injured followed up by liver, kidney, mesentry, bowel etc. Studies in India by Vadodariya et al, 3 in Jordan by Hamidi et al 2 also showed spleen as the commonest organ to be injured in blunt injury abdomen. Chest injuries, fracture of pelvis and spine were the maximum associated injuries.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The accuracy of CT in haemodynamically stable BAT has been well established. Sensitivity between 92% and 97.6% and specificity as high as 98.7% have been reported in patients subjected to emergency [5] .…”
Section: Introductionmentioning
confidence: 99%